Mechanical simulation of shield-machine empty-pushing through mine excavation section. Issue 3 (October 2021) - Zheng, Yiwu; Li, Zilin; Li, Yuan; Wang, Peitao; Ren, Fenhua
Abstract: During the empty-pushing process, pea gravel is generally used as a landfill to provide a reaction force to ensure that the shield-machine can pass through the risk area stably. The whole empty-pushing process involves the interaction and intercoupling between the pea gravel pile and the shield-machine. In this paper, the designs of shield-machine empty-pushing and shield-machine attitude were numerically analyzed and optimized based on the actual excavation process of Guangdong Rail Transit Line 21 in China. The conclusions are as follows: (1) during the tunneling process of the shield, the pea gravel pile underwent three stages: compaction, slipping, and balance. (2) As the height of the pea gravel landfill increased, the reaction force provided by the pea gravel gradually increased. (3) The filling height of pea gravel determined the force of the shield cutter-head and the thrust output of jacks. The stress distribution on the cutter-head was uneven, and the jack of various parts needed a different thrust output. When different shield-machines of various sizes were used for empty-pushing in several projects, the filling height of the pea gravel should be 60%–80% of the diameter of the shield-machine.